Analisa dan Perancangan Sistem Informasi Sekolah Terintegrasi Media Sosial sebagai Media Promosi - Nur Wachid Hidayatulloh; Prita Dellia; Nuru Aini (Jurnal Ilmiah Informatika, 2023)
In the era of the industrial revolution 5.0, many changes occurred in various fields one of the revolution is information system. The information system discussed this time refers to an agency's information system in schools. SMK PGRI 1 Bangkalan is one of the schools at the vocational secondary education level in Bangkalan Regency which does not yet have a website-based information system and has a total of no more than 50 students. A website-based information system can be a recommendation in overcoming these problems. This system can be used by the school to disseminate information about SMK which can be used as a promotional medium and will be integrated directly with social media. This study uses the waterfall model which is analogous to a waterfall. The waterfall model is used as a model reference in developing an information system. The results of this study are the design of a school information system that is integrated by social media account as a promotional medium in the form such as use case diagrams, flowcharts, database designs, and website interface designs.